Financial inclusion, mobile money and regulatory architecture - Martina Metzger; Maureen Were; Jennifer Pédussel Wu (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2022)
This paper discusses first the role of mobile money accounts to enhance financial inclusion towards vulnerable groups in developing countries in the light of recent empirical evidence. Second, we explore the role of regulation to address risks to consumers and the financial system arising from the use of mobile money accounts, a question which has not been thoroughly addressed in the literature. Although financial inclusion via mobile money accounts is increasing, the outreach to particular disadvantaged and poor groups is still limited. However, remittances and G2P payments might develop into game changers for financial inclusion of poor and vulnerable households. Many countries from Sub-Saharan Africa are outperformers in terms of use of mobile money accounts in comparison to developing countries in other regions. Strikingly, the empirical evidence suggests that the regulatory landscape was of strategic importance to unleash the developmental potential of mobile money networks and the crowding-in of formerly unbanked households. Regulation on consumer protection particularly is of strategic relevance for the lasting acceptance and smooth operation of mobile money services and sharing the benefits with disadvantaged and poor households. A lack of effective and convincing consumer safeguards in place could diminish the trust in mobile money services and subsequently their acceptance and use. As mobile money services involve similar risks as traditional banking services, similar rules should apply. In addition, there are risks arising from the particular technology for mobile money account holders and institutions of the financial sector, including DFS providers. To these risks belong hysteresis effects to the disadvantage of poor households due to the use of alternative data and biased algorithms as well as displacement effects in local traditional and digital financial services due to BigTech.
Keywords: D18; G18; G23; G51; G59; 330; Mobile money; financial inclusion; regulation; consumer protection; digital financial services; Big Data; Sub-Saharan Africa